1997
DOI: 10.1002/(sici)1097-4687(199711)234:2<131::aid-jmor2>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Sperm storage in the spermatheca of the red-back salamander,Plethodon cinereus (Amphibia: Plethodontidae)

Abstract: In northern Indiana, the mating season of Plethodon cinereus occurs after hibernation from March until June, when oviposition begins. During the mating season, a female stores sperm in its spermatheca, a compound tubular gland in the roof of the cloaca. The apical cytoplasm of the spermathecal epithelium is filled with large secretory vacuoles whose product is released while sperm are stored. Females induced to oviposit in June and July by injections of human chorionic gonadotropin (hCG) still retain much sper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…If mating activity in the Indiana population did commence in October, it would be interrupted by hibernation from November into March. Sever () found sperm in the Wolffian ducts of male P. cinereus in October, but Sever () did not find sperm in spermathecae of females from this locale in October. Sever () suggested that mating activity is most intense after hibernation until June, when oviposition commences.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…If mating activity in the Indiana population did commence in October, it would be interrupted by hibernation from November into March. Sever () found sperm in the Wolffian ducts of male P. cinereus in October, but Sever () did not find sperm in spermathecae of females from this locale in October. Sever () suggested that mating activity is most intense after hibernation until June, when oviposition commences.…”
Section: Discussionmentioning
confidence: 96%
“…Sever (1978) found sperm in the Wolffian ducts of male P. cinereus in October, but Sever (1997) did not find sperm in spermathecae of females from this locale in October. Sever (1997) suggested that mating activity is most intense after hibernation until June, when oviposition commences. Mental glands can develop in female Eurycea quadridigitata injected with a testosterone solution (Sever 1976b).…”
Section: Discussionmentioning
confidence: 99%
“…Dispersal patterns of offspring and relatedness of neighbouring individuals are not known for this species. The red‐backed salamander breeds in the spring ( Sever 1997) and females deposit their eggs in Jun. ( Blanchard 1928, pers.…”
Section: Introductionmentioning
confidence: 99%
“…(Sever and Hamlett 1998) and in Eurycea cirrigera (Sever 1992b) and Plethodon cinereus (Sever 1997); in the ambystomatid Ambystoma opacum (Sever and Kloepfer 1993); and in the salamandrids Salamandrina terdigitata (Brizzi et al . Degenerating sperm associated with an apocrine bleb.…”
Section: Comparative Biology Of Spermiophagymentioning
confidence: 99%
“…Abbreviations: Ab, apocrine bled; Af, axial fibre; Cl, cleavage line; Ds, desquamated epithelium; Ic, intercellular canaliculi; Lu, lumen; Myn, myoepithelial cells nucleus; Mv, microvilli; Nu, nucleus of an epithelial cell; Sn, sperm nucleus; Sp, sperm; Sv, secretory vacuoles. (Sever and Hamlett 1998) and in Eurycea cirrigera (Sever 1992b) and Plethodon cinereus (Sever 1997); in the ambystomatid Ambystoma opacum (Sever and Kloepfer 1993); and in the salamandrids Salamandrina terdigitata (Brizzi et al . 1995) and Notophthalmus viridescens (Sever et al .…”
Section: Comparative Biology Of Spermiophagymentioning
confidence: 99%